The Livelihoods Impacts of Irrigation in Western Africa: The Ghana Experience - Akudugu, Mamudu Abunga; Millar, Katherine Kaunza-Nu-Dem; Akuriba, Margaret Atosina (Sustainability, 2021)
Although agriculture remains the mainstay of the African economy, it is currently going through stress because of a multitude of factors including climate change. Thus, many countries in their efforts to transform their agricultural sectors are employing climate-smart initiatives including the provision of water harvesting technologies for irrigated crop production during the dry season. This paper examines the role of irrigation in the drive towards a transformation of smallholder agriculture in Africa. Focus group discussions, key informant interviews and individual questionnaires were employed for the data collection. The data were analyzed using the regression adjustment (RA) technique. The results indicate that irrigation has significant and positive impacts on farm incomes, employment, consumption, food security and non-farm businesses, all of which are necessary conditions for a successful transformation of smallholder agriculture in Africa. The impacts of irrigation on health and environmental sustainability are mixed—the positive being the ability of irrigators to pay for improved healthcare for their families and the negatives include the outbreak of waterborne diseases associated with irrigation water. Construction of irrigation facilities causes destruction to the environment but improves provisioning ecosystem services. It is generally concluded that access to irrigation is associated with higher farm incomes, employment, consumption, food security and engagement in non-farm business activities. The key policy implication of these findings is that African governments must formulate strategic policies that will accelerate investments in the provision of irrigation facilities to better promote the agenda to transform smallholder agriculture in the continent
Keywords: Africa; Ghana; irrigation; livelihoods; smallholder; ACE: Water, Irrigation and Sustainable Agriculture; Water & irrigation; University of Development Studies